2020
DOI: 10.6000/1929-7092.2020.09.41
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Expectation Inflation on Aggregate Demand: Examining the South African Inflation Expectation Channel of South African Monetary Policy

Abstract: South Africa targeted inflation since February 2000 as its monetary policy framework to ensure long-run price stability and continues to pursue a target of 3-6% for headline CPI inflation. Monetary policy emphasises the importance of promoting economic growth that can be sustained and maintenance of low inflation in an economy. Therefore, the paper seeks to check whether a relationship between economic growth (GDP) and expectation inflation exists. The autoregressive distributive lag (ARDL) econometric methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This is in line with economic theory, and the fiscal theory of price level because when consumers, as well as businesses, expect the inflation rate to rise in the future, this will increase their income tax, capital gains tax, and profits [14]. However, these findings differ from some studies that found a negative relationship though that study was between inflation expectation and aggregate demand [18].…”
Section: Findings and Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This is in line with economic theory, and the fiscal theory of price level because when consumers, as well as businesses, expect the inflation rate to rise in the future, this will increase their income tax, capital gains tax, and profits [14]. However, these findings differ from some studies that found a negative relationship though that study was between inflation expectation and aggregate demand [18].…”
Section: Findings and Discussionsupporting
confidence: 77%
“…Although a considerable amount of research has been conducted on the issues of public debt and expected inflation, there is a research gap on the impact of inflation expectations and public debt on taxation especially in South Africa [17][18][19]. For instance, there is a South African study that employed the Autoregressive Distributive Lag (ARDL) to evaluate the nexus between inflation expectations and aggregated demand using secondary time series data [18]. The study revealed that when employing the Error Correction Model (ECM), a 1% increase in inflation expectations would lead to a 0.4% decrease in the level of gross domestic product, ceteris paribus.…”
Section: Empirical Literaturementioning
confidence: 99%
See 3 more Smart Citations